PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA KORUPSI DANA TUNJANGAN KINERJA KEJAKSAAN NEGERI BANDAR LAMPUNG: Bambang Hartono 1 Zainudin Hasan 2 Wilsa Syahira 3 - Hartono, Bambang; Hasan, Zainudin; Wilsa Syahira (Universitas Kapuas, 2024)
ABSTRACT Corruption is a form of dishonesty or criminal act committed by a person or an organization entrusted with a position of power, to obtain illicit profits or abuse of power for one's personal gain. The problem in this research is what was the factor that caused the perpetrator to commit the criminal act of corruption in the performance allowance funds of the Bandar Lampung State Prosecutor's Office (Decision Study Number: 16/Pid.Sus-TPK/2023/PN.Tjk) Article 2 paragraph (1) Jo. Article 18 paragraph (1) of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes as amended by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes Jo. Article 55 paragraph (1) 1 of the Criminal Code Jo. Article 64 paragraph (1) 1 of the Criminal Code, Law Number 46 of 2009 concerning Corruption Crime Courts, Law Number 8 of 1981 concerning Criminal Procedure Law and other relevant statutory regulations, adjudicates This case decided to sentence the defendant to a prison sentence of 7 (seven) years and 6 (six) months minus the time the defendant was in custody, with an order that the defendant remain in detention.